Análisis de la satisfacción del adulto mayor ante el servicio de vacunas Covid-19 en el Centro de Salud Saquisilí. - Tapia Palma, Myriam Alexandra (2022)
The satisfaction of the service allows to cover the needs and expectations of the patient. This variable is essential for the institution, it plays an important role in reinventing itself and adapting to the new demands of the user. The problem is thatin the health center, vaccination coverage against Covid-19 in the older adults covers a smaller percentage of this group considered a priority within the inoculation process. Older adults have difficulty when applying Covid-19 vaccines, which affects the labor field. lifestyles. Therefore, the research work addresses the SERVQUAL model to study the five dimensions: reliability, responsiveness. warmth. security and tangibility. It allowed to establish if the patients are satisfied with the services offered in the institution. The approach in which the study is framed is the qualitative approach since it is desired to find links between the variables. The aforementioned analysis of user satisfaction was carried out using statistical methods. In addition, the level of research used in the project is the descriptive level, since it is intended to detail customer satisfaction in the area of vaccination. The results obtained in the investigation are the respective analyzes for each dimension of the SERVQUAL model for the health center and by identifying the scores, averages and percentages of each of them. a satisfaction analysis was established.